2001
DOI: 10.1099/00221287-147-4-879
|View full text |Cite
|
Sign up to set email alerts
|

The role and relevance of phospholipase D1 during growth and dimorphism of Candida albicans

Abstract: The phosphatidylcholine-specific phospholipase D1 (PLD1) in Saccharomyces cerevisiae is involved in vesicle transport and is essential for sporulation. The gene encoding the homologous phospholipase D1 from Candida albicans (PLD1) was used to study the role of PLD1 in this pathogenic fungus. In vitro and in vivo expression studies using Northern blots and reverse transcriptase-PCR showed low PLD1 mRNA levels in defined media supporting yeast growth and during experimental infection, while enhanced levels of PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 56 publications
2
56
0
1
Order By: Relevance
“…Earlier experiments performed in this laboratory have shown that PLD1 plays a significant role in the morphogenetic process (Hube et al, 2001 ;McLain & Dolan, 1997). Given that the product of PLD1 catalysis is PA At -25n8 11n1 18n9 22n2 19n2 21n5 20n9 17n2 74n8 14n3 17n3 20n9 20n4 Ca -12n3 23n9 22n3 21n5 21n9 22n1 21n1 27n8 10n1 48n5 45n2 24n1 Ce -11n3 10n9 11n0 11n7 11n2 12n1 10n4 10n5 10n7 11n7 12n3 Dm -49n2 41n5 44n2 46n3 38n7 19n6 10n5 15n1 18n7 19n7 Hsα -59n9 60n1 91n4 65n8 23n5 10n5 22n0 24n3 24n1 Hsβ -95n9 56n2 57n6 18n8 10n3 17n3 18n3 23n4 Mmα -56n6 60n3 19n9 9n4 18n6 22n1 23n2 Mmβ -63n4 22n0 10n3 19n8 23n6 23n4 Mmγ -17n7 12n4 14n5 19n2 23n6 Nr -17n3 18n5 20n5 22n4 Os -11n...…”
Section: Pi4p5k Activity Is Stimulated During Morphogenesismentioning
confidence: 94%
See 3 more Smart Citations
“…Earlier experiments performed in this laboratory have shown that PLD1 plays a significant role in the morphogenetic process (Hube et al, 2001 ;McLain & Dolan, 1997). Given that the product of PLD1 catalysis is PA At -25n8 11n1 18n9 22n2 19n2 21n5 20n9 17n2 74n8 14n3 17n3 20n9 20n4 Ca -12n3 23n9 22n3 21n5 21n9 22n1 21n1 27n8 10n1 48n5 45n2 24n1 Ce -11n3 10n9 11n0 11n7 11n2 12n1 10n4 10n5 10n7 11n7 12n3 Dm -49n2 41n5 44n2 46n3 38n7 19n6 10n5 15n1 18n7 19n7 Hsα -59n9 60n1 91n4 65n8 23n5 10n5 22n0 24n3 24n1 Hsβ -95n9 56n2 57n6 18n8 10n3 17n3 18n3 23n4 Mmα -56n6 60n3 19n9 9n4 18n6 22n1 23n2 Mmβ -63n4 22n0 10n3 19n8 23n6 23n4 Mmγ -17n7 12n4 14n5 19n2 23n6 Nr -17n3 18n5 20n5 22n4 Os -11n...…”
Section: Pi4p5k Activity Is Stimulated During Morphogenesismentioning
confidence: 94%
“…C. albicans strains used were CAF2-1 (ura3 ::imm434\URA3) and JDC12 (strain also designated pld1∆1 in Hube et al, 2001 ;ura3 ::imm434\ ura3::imm434 pld1::hisG::URA3::hisG\pld1 ::hisG), which are isogenic except as indicated (Hube et al, 2001). S. cerevisiae strains used were 23567 (a\α his3∆1\his3∆1 leu2∆0\ leu2∆1 met15∆0\j lys2∆0\j ura3∆0\ura3∆0 mss4 : : Kan R \ j ; Research Genetics), SEY6210.1 and AAY202.1 (SEY6210.1 with mss4∆ ::HIS3MX6 carrying YEplac-mss4-102).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dimorphic transition is regulated by a number of signal transduction pathways such as the MAPK and cAMP/protein kinase A pathways (reviewed by Sudbery et al, 2004;Whiteway & Oberholzer, 2004). In addition, lipid signalling pathways with second messengers such as DAG may play a role during morphogenesis of C. albicans (Hube et al, 2001).…”
Section: Introductionmentioning
confidence: 99%